Statistical Approach: Understanding the Effects of Preview, Question, Read, Reflect, Recite, Review (PQ4R) on Academic Achievement of Students in English - Khan, T. S.; Jehangir, M.; Niwaz, A.; Khan, M. M.; Shahzad, M.; Khan, M. S. (The Nucleus, 2018)
English is an international language, but still many countries (where English is a second language) are facing problems in academics. Whereas, Urdu is the national and most common language in Pakistan, so it is hard for students to get a good command on the subject of English. Additionally, reading comprehension is also a major issue with Pakistani students, as their teachers are unaware of the cognitive and metacognitive strategies to make learning interesting and long lasting. The recent study has been conducted to compare the effectiveness of PQ4R on the academic achievement of students in the subject of English. The sample constituted total hundred students; including fifty boys and fifty girls, studying in Telecom boy’s school and Telecom girl’s school, respectively. A statistical approach with pre-test and post-test through Cronbach alpha; 0.76 and 0.79, respectively, was used to evaluate PQ4R strategy on 10th grade students. The statistical output revealed that PQ4R strategy improved the performance of high achievers as well as low achievers among the targeted sample.